2021
DOI: 10.1523/eneuro.0481-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of VGLUT1 in Cholinergic Medial Habenula Projections Increases Nicotine Self-Administration

Abstract: Cholinergic projections from the medial habenula (MHb) to the interpeduncular nucleus (IPN) have been studied for their complex contributions to nicotine addiction and have been implicated in nicotine reinforcement, aversion, and withdrawal. While it has been established that MHb cholinergic projections co-release glutamate, no direct evidence has demonstrated a role for this glutamate projection in nicotine consumption. In the present study, a novel floxed Slc17a7 (VGLUT1) mouse was generated and used to c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The GFAP creERT2 gene was always maintained in heterozygosis. To produce a conditional allele of the mouse Slc17a7 gene encoding VGLUT1, GFAP creERT2 tdTomato lsl/lsl mice were back-crossed with Slc17a7 fl/fl mice 38 to obtain GFAP creERT2 Slc17a7 fl/fl tdTomato lsl/lsl mice and Slc17a7 fl/fl tdTomato lsl/lsl littermates. Likewise, to produce GFAP CreERT2 Slc17a6 fl/fl tdTomato lsl/lsl mice, we back-crossed GFAP creERT2 tdTomato lsl/lsl mice to VGLUT2-flox mice ( Slc17a6 fl/fl ; B6;129/Sv-Slc17a6tm1.1Edw, Jackson, 636372 48 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GFAP creERT2 gene was always maintained in heterozygosis. To produce a conditional allele of the mouse Slc17a7 gene encoding VGLUT1, GFAP creERT2 tdTomato lsl/lsl mice were back-crossed with Slc17a7 fl/fl mice 38 to obtain GFAP creERT2 Slc17a7 fl/fl tdTomato lsl/lsl mice and Slc17a7 fl/fl tdTomato lsl/lsl littermates. Likewise, to produce GFAP CreERT2 Slc17a6 fl/fl tdTomato lsl/lsl mice, we back-crossed GFAP creERT2 tdTomato lsl/lsl mice to VGLUT2-flox mice ( Slc17a6 fl/fl ; B6;129/Sv-Slc17a6tm1.1Edw, Jackson, 636372 48 ).…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether astrocyte release occurred through exocytosis, we sought to impede glutamate filling in vesicles. We took advantage of a recently developed Slc17a7 fl/fl mouse line 38 carrying a conditional allele of Slc17a7 , encoding VGLUT1, the main VGLUT isoform in hippocampus 35 , expressed also in glutamatergic astrocytes (Fig. 1e,g ; Extended Data Figs.…”
Section: Imaging Glutamate-secreting Astrocytesmentioning
confidence: 99%
“…According to our co-citation analysis, the medial habenula cholinergic system has attracted current attention because of its potential relationship between the MHb and nicotine withdrawal, drug addiction, and mood disorders ( McLaughlin et al, 2017 ; Lee et al, 2019 ). Moreover, MHb-IPN (interpeduncular nucleus) pathway showed left-right functional asymmetry in the level of neurotransmitter acetylcholine ( Hong et al, 2013 ), which also revealed the involvement of this pathway in nicotine addiction ( Souter et al, 2022 ). Notably, the CHRNA5 gene encoding the nicotinic receptor alpha 5 subunit, which is strongly implicated in smoking dependence, is expressed at highest mRNA levels in the IPN, while the A3/B5 genes encoding channel-forming α3 and β4 receptor subunits are prominently expressed in the ventral MHb ( Morton et al, 2018 ).…”
Section: Discussionmentioning
confidence: 97%
“…Within the mesolimbic circuit, nicotine facilitates glutamate release from presynaptic terminals in both the VTA and NAc, which is believed to play a role in its reinforcing actions [ 120 ]. Evidence suggests that blocking glutamatergic transmission within these brain circuits attenuates nicotine reward-related behaviors in rodents [ 120 , 125 , 126 ]. Conversely, facilitation of inhibitory GABAergic transmission attenuates nicotine seeking behaviors in rodent models of tobacco dependence [ 120 , 127 , 32 ].…”
Section: Preclinical Model-based Discovery Of Novel Targets For Smoki...mentioning
confidence: 99%